Sistem Informasi Pendataan Disabilitas pada Yayasan Pilar Purbalingga - Nur Chasanah; Leo Aditya Caesar (Politeknik Negeri Cilacap, 2020)
The development of technology is very helpful in data collection activities. Currently, a lot of data is circulating, but the amount is not in accordance with the data in the field. The information system can help in a more effective and efficient data collection process, in this research related to data collection on disability. Disability Data Collection Information System is a system created to collect data related to foundation management, foundation activities, biodata of persons with disabilities, types of disabilities, skills or training that have been participated in, list of assistance received by disabilities, and volunteer disabilities. The data will be used by the PILAR Purbalingga Foundation to support its activities in the disability domain. From these data can be used as a reference in carrying out activities that will be carried out at the foundation. The output produced from this study is the Disability Data Collection Information System at the Purbalingga PILAR Foundation which produces information related to data on persons with disabilities, volunteers and activities that are suitable for the needs of persons with disabilities under the PILAR Purbalingga Foundation. Data collection methods are carried out through observation and interviews with the manager of the foundation and persons with disabilities. The system development method used is a waterfall, the programming language used is PHP and MySQL for database processing in this study.